Pengelolaan Biaya Pendidikan Di SMP Negeri 1 Grobogan Tahun Pelajaran 2015/2016 - , Sudarmanto; , Prof. Dr.Sutama, M.Pd; , Dr. Suyatmini, M.Si (2017)
This study aims to: To describe (1) describe the planning education costs in SMP Negeri 1 Grobogan. (2) describe the realization of the of educational costs. And for (3) describe the responsibilities of education costs in SMP Negeri 1 Grobogan. This type of research is qualitative research design using an ethnographic approach. Results of the study show that (1) Planning starts the financial team SMPN 1 Grobogan make a budget plan of education that the source of funds received by the school from four sources, namely one the BOS from the government.Determination of the cost of the education received in February.. (2) Actual cost SMPN 1 Grobogan intended for direct and indirect spending. Realization of cost education for direct expenditures prepared in accordance with the need to finance 14 programs of activities, carried out in January and use is made after management fees liquid in February, has been set in use per three months. (3) Principal and the treasurer is responsible for cost education in SMP N 1 Grobogan. Principal at SMPN 1 Grobogan role as the budget and treasurer serve to dilute the cost education. Aspects which accounted manage cost education in the School in SMP N 1 Grobogan include legality of law and also aspects of cost education usefulness. A report compiled containing the recapitulation of the use of the ecuducation of indirect costs and direct along with details